2015
DOI: 10.1159/000442416
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Third Molar Impaction Pattern and Associated Clinical Symptoms in a Central Anatolian Turkish Population

Abstract: Objectives: The purpose of this study was to assess the pattern of third molar impaction and associated symptoms in a Central Anatolian Turkish population. Material and Methods: A total of 2,133 impacted third molar teeth of 705 panoramic radiographs were reviewed. The positions of impacted third molar teeth on the panoramic radiographs were documented according to the classifications of Pell and Gregory and of Winter. The presence of related symptoms including pain, pericoronitis, lymphadenopathy and trismus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
71
1
12

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(118 citation statements)
references
References 22 publications
12
71
1
12
Order By: Relevance
“…In addition, studies in different racial and ethnic groups have produced different results. In Bhopal, India [19], Saudi Arabia [1] the Anatolian Turkish Population, [13] and the present study, the vertical position is seen at the highest rates, while the mesioangular position is seen at higher rates in the Northeast Of Iran [18], Oman [7], India, [20] and Saudi Arabia [1]. In Saudi Arabia [1], the vertical position is higher at the maxilla, and the mesioangular position is higher at the mandible (Table 4).…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…In addition, studies in different racial and ethnic groups have produced different results. In Bhopal, India [19], Saudi Arabia [1] the Anatolian Turkish Population, [13] and the present study, the vertical position is seen at the highest rates, while the mesioangular position is seen at higher rates in the Northeast Of Iran [18], Oman [7], India, [20] and Saudi Arabia [1]. In Saudi Arabia [1], the vertical position is higher at the maxilla, and the mesioangular position is higher at the mandible (Table 4).…”
Section: Discussionsupporting
confidence: 62%
“…Another study was performed in Turkey in the region of Anatolia, and that study also reported a high prevalence of third molar impaction in the vertical position [13]. Many studies have similar findings in international studies [13,[15][16][17][18][19]. In some studies, the most common angulation pattern was mesioangular in the mandible [7,18,20] (Table 4).…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…The upper and lower third molars are the last teeth to erupt, the most affected by tooth impaction problems. The main factors related to the impaction of third molars are the lack of space, limited bone development, presence of adjacent teeth, dense bone structure or excess of soft tissue (Yilmaz et al, 2016).…”
Section: Introductionmentioning
confidence: 99%